Nilai-Nilai Pendidikan Islam: Studi Komparasi Pendidikan Multikultural Indonesia dan Kanada - Mustakim, Iqbal; Yaim, Ahmad; Fitriyanti, Ovi; Maryamah; Kurniawan, M Riski (Moderasi : Journal of Islamic Studies, 2023)
Multicultural education in developed countries (Indonesia and Canada), especially in basic education, wants education that upholds human dignity by respecting and understanding the differences that each individual has. Comparison of multicultural education (Indonesia and Canada) First, each developed country (Indonesia and Canada) has similarities in multicultural education, namely wanting to eradicate acts of discrimination and uphold human rights fairly. Second,differences in multicultural education in Indonesia give a role to the Principal in monitoring the diversity of each student. In Canada, implementing multicultural education involves implementing an educational model that reconstructs cultural diversity